2022
DOI: 10.2147/idr.s348643
|View full text |Cite
|
Sign up to set email alerts
|

Different Nanotechnology Approaches for Ciprofloxacin Delivery Against Multidrug-Resistant Microbes

Abstract: The percentages of organisms exhibiting antimicrobial resistance, especially resistance to multiple antibiotics, are incessantly increasing. Studies investigated that many bacteria are being resistant to ciprofloxacin. This review addresses the current knowledge on nano-based ciprofloxacin delivery approaches to improve its effectiveness and overcome the resistance issues. Ciprofloxacin delivery can be modified by encapsulating with or incorporating in different polymeric nanoparticles such as chitosan, PLGA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…It's noteworthy to mention that, other studies that have used of nanoplatforms for enhancement of ciprofloxacin efficacy are presented in Table 4 . Based on this table and mentioned studies, ciprofloxacin delivery can be modified by encapsulating with or incorporating different polymeric NPs such as poly lactic-co-glycolic acid (PLGA), chitosan, arginine, albumin, and other organic and inorganic nanostructure systems ( 179 ). Furthermore, studies have also shown that nano-platforms could enhance the efficiency of ciprofloxacin against bacterial cells, interfere with the biofilm community, enhance the penetration and protect the drug from deactivation or efflux ( Figure 4 ).…”
Section: The Combine Use Of Ciprofloxacin With Different Antibacteria...mentioning
confidence: 99%
“…It's noteworthy to mention that, other studies that have used of nanoplatforms for enhancement of ciprofloxacin efficacy are presented in Table 4 . Based on this table and mentioned studies, ciprofloxacin delivery can be modified by encapsulating with or incorporating different polymeric NPs such as poly lactic-co-glycolic acid (PLGA), chitosan, arginine, albumin, and other organic and inorganic nanostructure systems ( 179 ). Furthermore, studies have also shown that nano-platforms could enhance the efficiency of ciprofloxacin against bacterial cells, interfere with the biofilm community, enhance the penetration and protect the drug from deactivation or efflux ( Figure 4 ).…”
Section: The Combine Use Of Ciprofloxacin With Different Antibacteria...mentioning
confidence: 99%
“…Researchers have developed different strategies to improve the therapeutic effectiveness of cipro oxacin and overcome the resistance issue, of them, targeting cipro oxacin more precisely to the site of infection by using carriers. Cipro oxacin-nanoparticles conjugation, cipro oxacin nanoencapsulation, loading cipro oxacin in liposomes, and polymeric nanoformations are among the different promising nanotechnology-based approaches to combat cipro oxacin resistance [50]. In conclusion, isolates of Genus Enterobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin (CIPRO), a small molecular drug, is a broad-spectrum antimicrobial carboxyfluoroquinoline agent with demonstrated activity against most strains of Gramnegative bacteria and against certain Gram-positive bacteria [28]. CIPRO proved a powerful antibiotic to be applied for bone infections [29]. CIPRO hydrochloride powder of 99.5% purity was purchased from Gen Hunter (Nashville, TN, USA).…”
Section: Methodsmentioning
confidence: 99%